a scale Moral integrity the teacher kindergarten of the Kurdistan Region of Iraq) Constructing and applying) - Kurdistan Azeez Selman; Salwa Ahmad Ameen (Zanco Journal of Humanity Sciences)
This research aimed to the following objectives: Constructing a scale Moral integrity the teacher kindergarten  of the Kurdistan Region of Iraq and applying the scale of mental Moral integrity the teacher kindergarten  of the Kurdistan Region of Iraq Where the researcher used the descriptive method for its suitability to the nature of the research, and the Research Population includes the students of the kindergarten department in the universities of Kurdistan Region for the academic year (2021-2022) in the morning study. In order to achieve the objectives of the current research, the researcher built a measure of mental toughness, and for this purpose, the construction sample (statistical analysis) was selected from the original Population by 15%, as the construction sample amounted to (409) teacher. Where it was chosen by stratified random method, and after conducting the scale building procedures, the researcher built a scale to measure mental toughness consisting of (69) self-reporting items, distributed over (5) components, which included each of: Moral Discernment: (13, items), Consistent Behavior (14, items), Public Justification: (13, items), Empathy Respect (15, items), Social Compatibility (14, items), and it consists of (5) five answer alternatives, which extracted the appropriate psychometric properties of the scale items, which included: (discriminatory power, validity item, and reliability item), and the psychometric properties of the scale were extracted, which included: (face validity and constrict validity), and reliability: (The method of re-testing and the alpha-Cronbach equation), and to apply the scale in its final form, the researcher chose the applied sample from the original Population at a rate of (10%), as its number was (274) teacher, which were chosen by the stratified random method, by depending on Statistical Package of Social Sciences (SPSS) to analyze the data, the current research reached the most important results according to The objectives of the research included the following: Constructing a scale Moral integrity the teacher kindergarten  of the Kurdistan Region of Iraq which consists of (69) self-reporting items and is characterized by proper psychometric properties, And the teacher kindergarten  of the Kurdistan Region of Iraq are characterized by mental toughness in general and at a high level, and in conclusion and in light of the results of the research, the researcher reached some recommendations and suggestions.